Papers on the science of administration - Gulick, Luther Halsey, 1892-1993; Urwick, Lyndall F. (Lyndall Fownes), 1891-1983 (Early sociology of management and organizations, 2003)
This edited collection includes contributions by Follett, Fayol, Mooney, Dennison, Henderson, Whitehead and Mayo. The paper by Henderson, Whitehead and Mayo discusses the findings of the Hawthorne experiments.